Gain or amplification of 1q21 in systemic light chain amyloidosis is associated with advanced Mayo stage, plasma cell disease and worse overall survival - Oubari, Sara; Papathanasiou, Maria; Michel, Lars; Rassaf, Tienush; Thimm, Andreas; Hagenacker, Tim; Ehling, Daniela; Wieczorek, Stefan; Naser, Eyad; Hegenbart, Ute; Schönland, Stefan; Dührsen, Ulrich; et al. (Annals of hematology, 2025)
Systemic light-chain amyloidosis (AL) is an acquired protein misfolding disease characterized by deposition of immunoglobulin light-chain fibrils most often secreted from clonal plasma cells. In this retrospective study we analyzed the impact of iFISH aberrations on clinical characteristics and outcomes in 175 AL patients presented between 2015 and 2024. The most common aberrations were t(11;14) (57%), deletion 13q14 (33%), +1q21 (21%), hyperdiploidy (21%) and deletion 16q23 (17%). Significant elevations in dFLC levels were observed in patients with + 1q21 (median 407 vs. 213 mg/l, p = 0.04) and deletion 16q23 (median 476 vs. 204, p = 0.006). Only + 1q21 was associated with increased levels of cardiac biomarkers NTproBNP (median 9945 vs. 3538 pg/ml, p = 0.002) and hsTnT (median 110 vs. 53 ng/l, p = 0.002). This resulted in an increased proportion of patients with Mayo stage IIIb (53% vs. 26%, p = 0.01). Patients with + 1q21 had more advanced plasma cell disease (p = 0.0004). Our study highlights for the first time + 1q21 as the key aberration associated with advanced cardiac and plasma cell disease. After 17 months of follow-up, overall survival was significantly worse in patients with + 1q21 treated with daratumumab (7.2 months vs. not reached, p = 0.006). Alternative therapeutic approaches such as CAR-T therapies or bispecific antibodies should be further investigated.
Online veröffentlicht: 22. März 2025
Gesehen am 06.10.2025